Profiles and Predictors of Smart Home Technology Adoption by Older Adults. (October 2019) - Arthanat, Sajay; Wilcox, John; Macuch, Mackenzie
The commercial popularity of smart home (SH) technology has broadened the scope of aging-in-place and home health occupational therapy. The objective of this article is to examine ownership of SH technology by older adults, their readiness to adopt SH technology, and identify the client factors relating to the adoption. A survey of older adults aged 60 and above living in the community was conducted. Respondents ( N = 445) who were women; in the age group of 60 to 70 years; living in a two-level home, with a body function impairment; with a fall history; and experienced in information and communication technology (ICT) were significantly likely to be "brisk adopters" of SH ( p < .05). Stepwise regression model identified marital status, home security, and overall ICT ownership as the predictors of SH ownership, whereas being female, concern over home security, and perceived independence contributed to SH readiness ( p < .05). Consideration of the identified client profiles, health, and personal factors will strengthen SH integration for aging-in-place.